AB0418 The effect of concomitant methotrexate on serum tnf inhibitors levels and clinical response in patients with rheumatoid arthritis is dose dependent and greater than other dmards. (12th June 2018) - Martinez-Feito, A.; Plasencia, C.; Navarro-Compan, V.; Hernández-Breijo, B.; Gonzalez, M.A.; Monjo, I.; Nuño, L.; Nozal, P.; Pascual-Salcedo, D.; Balsa, A.
Abstract : Background: Several factors influence on the pharmacokinetics(PK) of TNF inhibitors(TNFi). One of the most relevant influencing factors is the development of antidrug- antibodies(ADA), which is associated with low circulating drug levels and loss of clinical efficacy. Previous studies, mostly about Adalimumab (Ada), have demonstrated a beneficial effect of concomitant use of methotrexate(MTX) in patients(pts) under TNFi therapy by reduction of immunogenicity. There are other csDMARDs(OD) as leflunomide, hydroxycloroquine or sulfasalazine which may have also an effect on PK. Objectives: To investigate the effect of csDMARDs on the presence of serum TNFi levels and on the clinical response during the first year of Ada or Infliximab(Ifx) treatment in RA pts. Secondly, to evaluate if MTX has a dose-dependent effect on these outcomes. Methods: This is an inception cohort including pts with RA starting Ifx or Ada in a tertiary hospital since 1999. At baseline, 6 and 12 months clinical(DAS28, EULAR response and ΔDAS28) and serological(drug and ADA levels) parameters were measured. Patients were clustered according to the use of concomitant csDMARDs at baseline in three groups: i)TNFi monotherapy;ii)TNFi +MTX;iii)TNFi +OD. Pts within the TNFi +MTX group were also classified according to the MTX dose:MTX <15 mg/week(TNFi +MTX <15) and MTX ≥15 mg/week(TNFi +MTX ≥15). Results: A total of 92 RA pts[Ada(n=25) or Ifx(n=67)] under TNFi were included. The number and percentage of pts in each group were as follows:TNFi monotherapy, 12 pts(13%);TNFi +MTX, 59 pts(64%);TNFi +OD 21 pts(23%). According to MTX dose, the distribution was:TNFi +MTX <15, 18 pts(20%);TNFi +MTX ≥15, 41 pts(45%). Considering the overall of pts receiving any dose of MTX, the percentage of them with drug levels after 12 months(71%) was numerically higher than in the other groups(20% in TNFi +OD and 9% in TNFi monotherapy, p=0.1). However, after stratifying pts by MTX dose, we observed that circulating drug levels at 12 months were more frequent in higher dose of MTX(54% of the pts with TNFi +MTX ≥15) compared to patients with TNFi +MTX <15 (17%), with TNFi +OD(20%) and with TNFi monotherapy (9%);p=0.002). According to EULAR response, pts treated with TNFi +MTX(81%) achieved more frequently a good response compared with the other groups (11% on TNFi +OD and 8% on TNFi monotherapy, p=0.6). Moreover, differences on clinical response were observed depending on MTX dose. While 58% with TNFi +MTX ≥15 were good EULAR responders, 23% with TNFi +MTX <15 achieved this. Overall, the best effect on clinical response was observed in the group of MTX; p=0.4. Finally, the TNFi median survival time(mst) was significantly higher in pts with TNFi +MTX than in pts with TNFi +OD or on TNFi monotherapy(5 years vs 2 years vs 2.15 years, respectively;p=0.03). Analysing by MTX dose, drug survival was superior for high (≥15)and low MTX doses(<15) (mst 5.2 and 3.3, respectively)compared to OD and/or TNFi monotherapy although the difference was not statistically significant p=0.09. Conclusions: In RA pts under Ifx or Ada treatment, the presence of TNFi in serum, the clinical response and the TNFi survival are influenced by MTX but not by OD. Moreover, a MTX dose-dependent effect is closely associated with these outcomes. Disclosure of Interest: None declared